An empirical research on the application of coconut leaf sheath on jewellery products / Mohd Faiz Jalaludin - Jalaludin, Mohd Faiz (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
This research focused on experimental application of recycle material on jewellery products. This research experimented on suitable techniques to be applied on recycle material of jewellery products and the suitability of the recycle material to be applied on jewellery products. This research aims on how to test the durability and suitability of the recycle material being applied on jewellery products. The researcher has chosen the coconut leaf sheath material to be applied on jewellery products. A variety of experiment has been done to coconut leaf sheath that produces improvement and added value to the recycle material and at the same time suitable to be applied on the jewellery products. This research was done based on the objective which is to generate a faster profit and side income while waiting for the slow coconut palm growing process, to fulfill the manufacturing industry that needs renewable raw material especially in fiber industry, to utilize the wastes of natural fiber into profitable and marketable raw material especially for rural entrepreneurs and to introduce the improvement and new added value of mix media method to Malaysia’s jewellery industry. The methodology used is experiment method in order to explore various options of technique and material used to achieve optimum results. The experiment includes coloring, shaping, forming, designing, and preserving that recycle material in order to make it ideal for application on jewellery products. The researcher only focused the experiment on the surface and not into micro molecule treatment just to make sure this experiment is easy to handle by anyone who is interested to commercialize it. This research concluded that the enhancement of recycle material will generate faster profit and provide side income to the rural coconut entrepreneurs and contribute to the development of renewable fiber in manufacturing industry. At the same time, it will provide a lot of work opportunities and a lot of vacancies for unemployed person. The researcher also concluded that the waste of natural fiber can be transformed into profitable material and the application of coconut leaf sheath on jewellery products with some new added value will be a spectacular identity of Malaysia as the largest agriculture country.